Application of the Water Evaluation and Planning (WEAP) Model to simulate current and future water demand in the Blue Nile - McCartney, Matthew P.; Ibrahim, Y. A.; Sileshi, Y.; Awulachew, Seleshi Bekele (2009)
The riparian countries of the Nile have agreed to collaborate in the development of its water resources for sustainable socioeconomic growth. Currently there is significant potential for expansion of hydropower and irrigation in the Blue Nile River in both Ethiopia and Sudan. However, the likely consequences of upstream development on downstream flows have not been fully assessed and the water resource implications of development in both countries are unclear. Against this background, the Water Evaluation And Planning (WEAP) model was used to provide an assessment of both the current situation and a future (2015) scenario. The future scenario incorporated new irrigation and hydropower schemes on the main stem of the Nile and its principal tributaries. Data for all existing and planned schemes were obtained from the basin master plans as well as from scheme feasibility studies. Water use was simulated over a 32-year period of varying rainfall and flow. Preliminary results indicate that currently irrigation demand in Sudan is approximately 8.5 Bm3y-1 for 1.16 million hectares (mha). This compares to a total irrigation demand in Ethiopia of just 0.2 Bm3y-1. By 2015, with many existing schemes being extended in Sudan and new schemes being developed in both countries, irrigation demand is estimated to increase to 13.4 Bm3y-1 for 2.13 mha in Sudan and 1.1 Bm3y-1 for 210 thousand hectares (tha) in Ethiopia. The flow of the Blue Nile is estimated to decline from an average of 46.9 Bm3y-1 to 44.8 Bm3y-1 at the Ethiopia-Sudan border and from a current average of 43.2 Bm3y-1 to 36.2 Bm3y-1 at Khartoum (including evaporation from all reservoirs). Although total flows are reduced, greater regulation results in higher dry season flows at both locations.